Vain Fortune: A Novel - Moore, George, 1852-1933; Greiffenhagen, Maurice, 1862-1931 (Salt Lake City, UT : Project Gutenberg, 2004)
"Vain Fortune" by George Moore is a novel written during the late 19th century. Set against the backdrop of London's theatre scene, it follows the life of Hubert Price, an aspiring playwright struggling with personal and financial difficulties as he strives to complete his latest work, "The Gipsy." The narrative captures the tension between artistic ambition and the harsh realities of life, exploring themes of disinheritance, love, and societal expectations. The opening of the novel introduces Hubert Price in his cluttered lodgings, immersed in a mix of personal turmoil and creative aspiration. We learn about his financial woes and that he is haunted by his failure to secure success with his previous plays. As he battles against his creditors and wrestles with his playwriting, the complexities of his relationships, particularly with fellow artist Rose Massey, unfold. Hubert's circumstances are exacerbated by the recent disinheritance by his wealthy uncle, which sets the stage for future conflict. At the same time, the narrative hints at the potential for redemption through the development of relationships and creative endeavors. Huberts's introspection and keen awareness of his plight invite readers to deeply engage with his journey. (This is an automatically generated summary.)
1895 Edition
Release date is 2004-06-01
Produced by Jon Ingram, Branko Collin and PG Distributed Proofreaders
Keywords: Inheritance and succession -- Fiction; Young women -- Fiction; Triangles (Interpersonal relations) -- Fiction; Dramatists -- Fiction; Unrequited love -- Fiction